2014
DOI: 10.1002/gps.4200
|View full text |Cite
|
Sign up to set email alerts
|

Reward‐related decision making in older adults: relationship to clinical presentation of depression

Abstract: Objective Impairment in reward processes has been found in individuals with depression and in the aging population. The purpose of this study was twofold: 1. To use an affective neuroscience probe to identify abnormalities in reward-related decision making in late-life depression. 2. To examine the relationship of reward-related decision making abnormalities in depressed, older adults to the clinical expression of apathy in depression. We hypothesized that relative to elderly, healthy subjects, depressed, elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
0
18
1
Order By: Relevance
“…Of the 5 studies included, 4 evaluated DM in young adults with MDD and 1 in older adults. Geographic heterogeneity can be observed in these studies, since 2 studies took place in the USA, 15 , 16 1 in Hungary, 17 1 in the United Kingdom, 18 and 1 in Portugal. 19 The samples of all of the selected studies can be considered relatively small, ranging from 39 to 96 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 5 studies included, 4 evaluated DM in young adults with MDD and 1 in older adults. Geographic heterogeneity can be observed in these studies, since 2 studies took place in the USA, 15 , 16 1 in Hungary, 17 1 in the United Kingdom, 18 and 1 in Portugal. 19 The samples of all of the selected studies can be considered relatively small, ranging from 39 to 96 participants.…”
Section: Resultsmentioning
confidence: 99%
“…We found an inverse relationship between depressive symptoms and the outcome sensitivity ( v ) parameter in individuals with OCD or HD. It is worth noting that previous studies of decision making under risk utilizing the IGT in MDD samples have yielded mixed results, with some studies finding greater levels of risk aversion in depressed participants relative to HC, while other studies found the opposite (Ernst, 2012; McGovern et al, 2014). …”
Section: Discussionmentioning
confidence: 96%
“…Half of the decks are disadvantageous (i.e., higher immediate rewards but long‐term negative outcomes) and the other half are advantageous (i.e., lower immediate rewards but long‐term positive outcomes). Overall, older adults with major depression do not differ from age‐matched controls on the Iowa or other gambling paradigms . However, older adults with major depression and clinical evidence of poor decision making (as evidenced by a history of attempted suicide) perform worse on a gambling task when compared to older depressed adults with no history of suicide .…”
Section: Future Investigationsmentioning
confidence: 86%
“…However, older adults with major depression and clinical evidence of poor decision making (as evidenced by a history of attempted suicide) perform worse on a gambling task when compared to older depressed adults with no history of suicide . In contrast, apathetic, depressed elderly patients are not influenced by immediate reinforcers (the high rewards of the disadvantageous decks) and demonstrate an advantageous strategy on the Iowa Gambling Task (selecting cards from the conservative decks) when compared to nonapathetic, depressed older adults . Elucidating the neurocognitive outcome of geriatric depression patients with behavioral disturbances mediated by ventromedial regions remains ongoing.…”
Section: Future Investigationsmentioning
confidence: 99%
See 1 more Smart Citation